Factors Affecting Bullying in Home and School Life: A Mixed Method Research - Hülya Kartal; Yakup Balantekin; Asude Bilgin; Mehmet Soyuçok (Anı Publishing, 2019)
In this research, it was aimed to determine the factors affecting the bullying in secondary school students' home and school life in a multifaceted and comprehensive manner with qualitative and quantitative approaches. The study group of this research was determined according to sequential mixed method (quantitative-qualitative) sampling, one of the mixed method research designs. In this context, for collection of the quantitative data, fifth-grade students studying in randomly-selected classes at 19 secondary schools located in the centre of Bursa and chosen by the probability sampling method made up the study group. The qualitative data were obtained from the answers given to the survey questions by students determined to have been subjected to bullying or to have engaged in bullying. The research findings reveal that male students engaged in bullying or were subjected to bullying at a significantly higher rate than female students. There was a positive relation between the engagement of the students' in out of school activities and not participating in any kind of bullying situations. It was found that there was a negative relationship between playing daily video or computer games and participation in bullying situations. It was also found a negative relationship between friendship relations and being in bullying anyhow. There was a strong negative relation between the avarage points of self evaluation of students and participating in bullying situations. Students were frequently exposed to physical and verbal bullying; that students who engaged in bullying did so because they were themselves made fun of and sworn at; that when bullying took place, both students who were subjected to bullying and those who engaged in bullying generally moved away from the scene and that bullying was generally carried out in places where and at times when teachers were absent.